Synergistic Effect of Metronidazole and Chlorhexidine against Porphyromonas gingivalis Growth: An In Vitro Study - Claudia Lorenzi; Fabrizio Lio; Vincenzo Mazzetti; Paolo Carosi; Stefano Lamelza; Enrico Salvatore Pistoia; Francesca Pica; Roberta Gaziano (MDPI AG, 2024)
Aim: To evaluate the potential synergistic activity of metronidazole (MTZ) and chlorhexidine (CHX) against Porphyromonas. gingivalis (P. gingivalis) growth. Methods: Antimicrobial susceptibility tests of P. gingivalis to MTZ and CHX were performed on in vitro serial 2-fold dilutions of MTZ (from 1 mg/mL to 0.015 mg/mL) and CHX (from 1 mg/mL to 0.03 mg/mL) in thioglycollate medium broth in a 96-well plate. The turbidity of each sample was analyzed by absorbance spectrophotometry at 450 nm wavelengths by using an enzyme-linked immunosorbent assay (ELISA) reader. The MIC50 (minimum inhibitory concentration) and MBC (minimum bactericidal concentration) were assessed. To investigate the potential synergism between MTZ and CHX, bacterial cells were treated with MTZ or CHX, as described above, either alone or in combination. Results: The MIC50 of MTZ was 0.03 mg/mL while that of CHX ranged from 0.12 to 0.06 mg/mL. MTZ and CHX exerted a significant inhibitory effect on P. gingivalis growth in a dose-dependent manner. MTZ at a low and ineffective concentration of 0.015 mg/mL, associated with a suboptimal concentration of CHX (0.03 mg/mL), exhibited a significant synergistic inhibitory effect on bacterial growth (50% inhibition vs. control) (p < 0.001), and the effect was more remarkable with 0.06 mg/mL CHX (75% inhibition vs. control). Conclusions: CHX and MTZ showed a significant synergistic effect against P. gingivalis growth. A non-effective concentration of MTZ (0.015 mg/mL) combined with suboptimal concentrations of CHX (0.03 mg/mL and 0.06 mg/mL) were related to a 50% growth in the inhibition and 99.99% death of P. gingivalis, respectively. The applicability of the clinical use of these concentrations should be tested in randomized controlled trials.